Islamic Legal Analysis of the Provision of Contraceptives for School-Aged Children and Adolescent Reproductive Health in Indonesia - Ediz, M.Hidayat; Viona Dwi Seftria Putri; Mulyani, Ridha; Zulfadli; Muhammad Irfan (As-Siyasi: Journal of Constitutional Law, 2026)
This study examines the controversy surrounding Article 103 paragraph (4) letter e of Government Regulation Number 28 of 2024, which includes the provision of contraceptives in reproductive health services for school-aged children and adolescents. The central issue is not merely the medical benefit of contraception, but how state policy is formulated when the constitutional duty to protect health intersects with Islamic moral principles and child protection. This study uses normative legal research, drawing on statutory and conceptual approaches. Primary legal materials include the 1945 Constitution, Law Number 17 of 2023, Government Regulation Number 28 of 2024, and child health regulations, while secondary materials include literature on Islamic law, Fiqh siyasah, maqasid al-shari’ah, and reproductive health studies. The analysis uses Fiqh siyasah dusturiyyah as the main framework and siyasah tanfidziyyah to assess policy implementation. The findings show that the regulation can be justified as a preventive health policy if it is interpreted restrictively and accompanied by clear criteria, parental or guardian involvement, counseling, education, and safeguards against misuse. Without such limits, the policy risks being perceived as permissive and inconsistent with the principle of Sadd al-dzari’ah. This article offers an integrative model between the state's responsibility for reproductive health and the protection of religion, lineage, life, reason, and child welfare based on maqasid.